Pain in preterm newborns submitted to music and 25% glucose intervention - Melo, Gleicia Martins de; Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2017)
Objective: o compare the pain response of preterm newborns submitted to arterial puncture who received musical intervention with those who received 25% glucose intervention.Methods: randomized, double-blind clinical trial; the sample consisted of 48 videos of preterm infants of the experimental group (music, n = 26), who listened to music for 10 minutes, and the control group (25% glucose, n = 22), who received 25% glucose two minutes before puncture. The pain was evaluated by the Neonatal Facial Coding System at moments: Baseline, Treatment, Painful, Recovery 1 and Recovery 2. Results: there were similarities between groups at the moments Baseline, Recovery 1 and 2. A statistically significant difference was observed at the moment Treatment (p = 0.014), Painful (p = 0.029) for the control group. Conclusion: 25% glucose differed from music when comparing the pain response in the Treatment and Painful moments. Brazilian Registry of Clinical Trials: UTN: U1111-1123-4821.